SYSTEM OF VALUES IN AN IMPERFECT FAMILY WITHIN THE FRAMEWORK OF SCIENTIST THEORY (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article analyzes concepts such as "values" and "value orientations". Different approaches to the study of values are considered in psychology, philosophy, and sociology